ANALYSIS OF THERMAL PROPERTIES OF THE LED-LINES BY METHOD OF ELECTRICАL TRANSIENT PROCESSES - S. A. Manеgo; Yu. A. Bumai; I. A. Khorunzhii; Yu. V. Trofimov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Increasing the solid lighting facilities operational energy-efficiency in the national economy of the Republic of Belarus is of current concern. The modern problems of energy-saving lighting are multifaceted and broad-ranging. It is particularly burning amidst the energy crisis and the world commercial slump. Thus, the lighting demands 10–13 % of the total electric energy consumption in Belarus. That is to say, there is a significant potential of energy saving in transition to energy-efficient lighting. The paper considers the issues of reliability and service period of the solid-state lighting devices created on the basis of lines of light-emitting-diodes (LED) produced by Paragon Semiconductor Lighting Technology Co., Ltd. The optoelectronic apparatuses reliability assessment is based on investigation of the development principles and deterioration mechanisms leading to failures of one kind or another. The deterioration causes ascertainment is indispensable for acting upon them later on and thus reducing the degradation speed and extent. One of the LED-devices deterioration main sources is the temperature overheat of the LED-chip active area. Therefore, techniques for evaluating the heat characteristics of solid lighting devices become the issue of the day. The article investigates thermal properties of high-capacity blue LED-lines by method of electrical transient processes. The authors calculate temperatures in the LED-lines active areas at various heat-dissipation conditions and injection currents values. They realize computer generated simulation of the heated lines thermal fields applying the ANSYS packet. The study concludes that out of the degree of temperature-distribution heterogeneity along the line impossibility of the line chip structural units thermal characteristics extraction arises based on all LEDs homogenized over the line temperature-time dependences. The paper indicates that one can with reasonable accuracy obtain the LED-lines thermal parameters employing the line representation with two equivalent RC-strings corresponding the thermal ways ‘LED active area – aluminium base’ and ‘aluminium base – environment’. For these areas thermal time constants, thermal resistances and thermal capacities are determined.